2021
DOI: 10.3389/fpsyt.2021.705554
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Autism Research From Mice to Marmosets: Behavioral Development of Offspring Following Prenatal Maternal Immune Activation

Abstract: Understanding the mechanism(s) by which maternal immune activation (MIA) during gestation may disrupt neurodevelopment and increase the susceptibility for disorders such as autism spectrum disorder (ASD) or schizophrenia is a critical step in the development of better treatments and preventive measures. A large body of literature has investigated the pathophysiology of MIA in rodents. However, a translatability gap plagues pre-clinical research of complex behavioral/developmental diseases and those diseases re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…MIA is a primary link between maternal viral infection and offspring neurodevelopmental disorders Convergent data from animal models have demonstrated that MIA, rather than a specific virus or bacterial infection, is likely the final common pathway by which most maternal infections confer offspring neurodevelopmental morbidity [42,43]. Rodent and non-human primate models have utilized multiple techniques to activate the maternal immune system, including the viral mimic polyinosinic:polycytidylic (poly[I:C]), a synthetic double-stranded RNA, demonstrating alterations in offspring brain immune function, and behavioral and neuroimaging correlates of ASD and schizophrenia [42,[44][45][46][47][48][49][50][51][52][53].…”
Section: Mia and Placental Immune Activation In Response To Sars-cov-...mentioning
confidence: 99%
“…MIA is a primary link between maternal viral infection and offspring neurodevelopmental disorders Convergent data from animal models have demonstrated that MIA, rather than a specific virus or bacterial infection, is likely the final common pathway by which most maternal infections confer offspring neurodevelopmental morbidity [42,43]. Rodent and non-human primate models have utilized multiple techniques to activate the maternal immune system, including the viral mimic polyinosinic:polycytidylic (poly[I:C]), a synthetic double-stranded RNA, demonstrating alterations in offspring brain immune function, and behavioral and neuroimaging correlates of ASD and schizophrenia [42,[44][45][46][47][48][49][50][51][52][53].…”
Section: Mia and Placental Immune Activation In Response To Sars-cov-...mentioning
confidence: 99%
“…4.4 Marmoset maternal Poly IC models. The recently established marmoset MIA model ( 148 ) provides an opportunity to explore the impact of prenatal immune challenge in a species that is playing an increasing role in neurodevelopmental research. For a NHP, marmosets are comparatively small, have a higher reproductive efficiency with respect to gestation, delivery intervals, and litter size, and overall have a shorter life history and development, becoming sexually mature at around 1.5 years old ( 149 ).…”
Section: Nhp Models Of Maternal Infectionmentioning
confidence: 99%
“…This suggests that repertoire alteration might be more sensitive to this paradigm than the total number of calls. Although the meaning of the repertoire changes we found in our study is unknown, alteration in the vocal repertoire is a common finding in animal models of developmental disorders in rodents (Binder & Lugo, 2017;Nolan et al, 2020;Romano et al, 2013; and primates (Santana-Coelho et al, 2021), suggesting that these findings can have significant translatability.…”
Section: Discussionmentioning
confidence: 77%